Objective Scoring of Extent of Steatosis and Fibrosis Using Computer Assisted Image Analysis System in Liver Biopsy Of Non-alcoholic steatohepatitis Patients - Kinra, Prateek; Das, Prasenjit; Yadav, Rajni; Mallik, Saumyaranjan; ., Shalimar; Acharya, S K; Kumar, Guresh; K, Maneesh Vijay; Gupta, Siddhartha Datta (Annals of Pathology and Laboratory Medicine, 2018)
Background: The histological grading/staging system for Non-alcoholic steatohepatitis (NASH) encompasses the following criteria: extent of steatosis, lobular-inflammation, ballooning hepatocytes and extent of fibrosis. The existing scoring system has a drawback of high subjectivity. This study was designed with aims of studying (i) Inter & intra-observer variation; (ii) Correlation of the visual grading/staging with computer assisted image-analysis technique (IA); ultrasonography grade of fatty liver and fibroscan for extent of fibrosis. Methods:48 known cases of NASH were studied. The Sirius-red stained slides were assessed for % area of steatosis, fibrosis and parenchyma using Image Pro PlusÂ® 6.1 image-analysis software. Results: The Kappa coefficient value for inter-observer variation was 0.338 (SE: 0.111-fair agreement); intra-observer variation was -0.083 (SE: 0.143-poor agreement). There was no agreement between the steatosis scoring between visual grading and IA score (K= -0.16). IA score unlike visual score correlated well with the USG grading system (K= 0.65) and biochemical variables [P values TG (0.04), BMI (0.039)]. For the first time in literature image analysis fibrosis score has been assessed in cases of NASH. The correlation between fibroscan score and IA fibrosis showed good correlation (r=0.766). The paper also lays down the cut off values of %fibrosis score on image analysis. A linear progression curve has been plotted to estimate extent of actual fibrosis in liver as against the existing fibroscan test. Conclusion: Visual assessment over-estimates the area of steatosis, resulting in false higher NASH histological grade, unlike the image-analysis system. The image-analysis adds objectivity to score steatosis and fibrosis.